(untitled) (The Review of Diabetic Studies, 2025)
Background: The objective of the study was to formulate and Evaluate Diclofenac Diethylamine (DDEA) transdermal patch. Transdermal systems are an enhancement in the release of drug delivery because they enable the controlled release of medication through skin absorption. Method: This research seeks to develop Transdermal Films of Diclofenac Diethylamine employing Eudragit RL100, HPMC K100, HPMC K4M and Ethyl Cellulose. The solvents used were Ethanol, Methanol, Chloroform, and Water with PEG400 and Glycerin as the plasticizers. Patches were casted using the solvent casting method and designed using trial formulations of Eudragit RL100 with HPMC K100, HPMC K4M or Ethyl Cellulose. With the Eudragit RL100: HPMC K100 ratio, the batch was subsequently optimized with a methanolic solution of Diclofenac Diethyl amine for further refinement. Results: The evaluation was done based on physical appearance, thickness, weight uniformity, folding endurance, and surface pH. Two formulations (Eudragit RL100: HPMC K100 and Eudragit RL100: HPMC K4M) were tested for In vitro dissolution, with the former exhibiting superior drug release, more than the latter. The percentage cumulative drug release was plotted against time. Formulation F1 demonstrated superior dissolution characteristics compared to F2, with cumulative drug release values of 45.63% and 39.98%, respectively. Conclusion: It was concluded that it is the best choice, for fabrication of DDEA patches for the sustained release with better enhancement of DDEA.